The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1992
DOI: 10.3102/00028312029002425
|View full text |Cite
|
Sign up to set email alerts
|

Family and High School Experience Influences on the Postsecondary Educational Plans of Ninth-Grade Students

Abstract: The objectives of this study were to review the current literature on status attainment and student college choice and to develop and test a structural model of predisposition to attend college. Family and student background characteristics, parents' educational expectations for students, level of student involvement in school, and student achievement were cited as influences on students' predisposition toward postsecondary education and were the chief components of the model. Data from 2,497 ninth-grade stude… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

15
171
2
4

Year Published

2004
2004
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 263 publications
(192 citation statements)
references
References 30 publications
15
171
2
4
Order By: Relevance
“…For example, in a study of South African parents' expectations about the long-term attainment of their 11th grade children, parental expectations were related to literacy/numeracy scores in eighth grade for "Whites" but not for "Blacks," after controlling for parents' education (Beutel and Anderson 2008). Similar findings emerged in the USA, where Hossler and Stage (1992) found that minority parents had higher educational expectations than European American parents even though the GPAs of their ninth graders were lower than those of European Americans.…”
Section: What Are the Predictors Of Parental Expectations?supporting
confidence: 59%
See 1 more Smart Citation
“…For example, in a study of South African parents' expectations about the long-term attainment of their 11th grade children, parental expectations were related to literacy/numeracy scores in eighth grade for "Whites" but not for "Blacks," after controlling for parents' education (Beutel and Anderson 2008). Similar findings emerged in the USA, where Hossler and Stage (1992) found that minority parents had higher educational expectations than European American parents even though the GPAs of their ninth graders were lower than those of European Americans.…”
Section: What Are the Predictors Of Parental Expectations?supporting
confidence: 59%
“…Students whose parents hold high expectations receive higher grades, achieve higher scores on standardized tests, and persist longer in school than do those whose parents hold relatively low expectations (Davis-Kean 2005;Pearce 2006;Vartanian et al 2007). High parental expectations are also linked to student motivation to achieve in school, scholastic and social resilience, and aspirations to attend college (Hossler and Stage 1992; …”
mentioning
confidence: 99%
“…For example, socioeconomic status (SES) has a significant impact on college choice. Several studies have found that students from high SES background are more likely to attend college than students from low SES backgrounds (Hossler, Schmit, & Vesper, 1999;Hossler & Stage, 1992;McDonough, 1997;Paulsen, 1990;Stage & Hossler, 1989;Tuttle, 1981). In addition, family and peers play a large role college choice.…”
Section: College Choice Modelmentioning
confidence: 99%
“…Parental education matters as well. Students with parents who have more formal education are more likely to have college aspirations and attend college (Bouse & Hossler, 1991;Conklin & Dailey, 1981;Davies & Kandel, 1981;Hossler & Stage, 1992;Stage & Hossler, 1989;Tuttle, 1981). Likewise, students who have peers attending college are more likely to attend college (Carpenter & Fleishman, 1987;Davies & Kandel, 1981;Tillery, 1973).…”
Section: College Choice Modelmentioning
confidence: 99%
“…Numerous studies conclude that the influence of family greatly affects the future educational aspiration of students (McDonough, 1997;Jun & Colyar, 2001;Plank & Jordan, 2001;Gandara, 2002). Parents influence the decision of participation in higher education through the various roles they play: promoters and encouragers of particular behaviours, providers of resources, and role models (Conklin & Dailey, 1981;Hossler & Stage, 1992;Engle, 2007;McCarron & Inkelas, 2006;Lohfink & Paulsen 2005;Pike & Kuh 2005;Choy2001;Terenzini et al, 1996;London, 1996;Riehl, 1994;Pratt & Skaggs, 1989;Bilson & Terry 1982;Volle & Federico, 1997). However, offering parental support means engaging in decision making, asking pertinent questions, providing financial resources, and giving tangible support, which may include: arranging for college visitations, saving money for tuition, guiding the completion of applications and other forms, gathering information from college programs, and attending financial aid workshops (National Postsecondary Education Cooperative, 2007).…”
Section: Decision Of Going For Higher Education-economic Versus Socialmentioning
confidence: 99%